COMMUNITY SUPPORT AND CHALLENGES OF REINTEGRATING CHILDREN, WOMEN, AND FAMILIES RETURNING FROM IDP CAMPS IN NORTH-EAST NIGERIA - Nte, Ngboawaji Daniel (International Journal of Humanity Studies (IJHS), 2025)
This empirical paper examined support roles for communities and the challenges, risks, and barriers facing them in the reintegration of children, women and families returning from Internally Displaced Persons (IDP) camps in North-east Nigeria. The methodology adopted by this study was a qualitative research method namely phenomenological research design that used a series of semi-structured Key Informant Interviews (KII) and Focused Group Discussions to gather data for the study. For the interviews, a semi-structured interview was adopted. Data analysis was done using the Thematic Analysis approach. The findings of the study identified the key support needs of children, women, and family IDP returnees to include local community/family support, psychological/counselling support, schooling support, economic support, and whole-of-family support, among others. The results also identified key roles for communities in supporting comprehensively and ensuring the reintegration efforts of the IDP returnees.  The findings also highlighted that the communities need to provide significant support to the efforts at reintegration of the IDP returnees in terms of resources. Finally, the study recommends strong empowerment of the communities through information sharing and the provision of capacities and resources. The study also recommends that stakeholders strive to forge a strong bond of partnership that sees both the government and community role-players as important equal partners and co-drivers of the reintegration intervention.